Late Onset Takayasu Arteritis and Rheumatoid Arthritis - K. E. Verweij; A. M. E. van Well; J. W. vd Sluijs; A. Dees (Case Reports in Medicine)
We encountered the rare case of a 48-year-old Caucasian woman who developed Takayasu arteritis (TA) while suffering from seropositive rheumatoid arthritis (RA). Several studies have reported an association between TA and various autoimmune disorders, however, the concurrent presence of Takayasu arteritis and rheumatoid arthritis is described in only few cases in the literature to date. The exact nature of the relationship between TA and RA remains unknown. Perhaps the development of these two diseases represents non-specific systemic inflammatory changes in the presence of a hereditary background predisposing to both RA and TA.